Quality of life and compliance in geriatric patients - Kalugin, Igor (Psychosomatic Medicine and General Practice, 2017)
Background. Older adults usually have more than one chronic disease. In most cases, each condition requires constant pharmacotherapy. On average, the clinical examination of patients aged 60 and older reveals at least four or five different chronic pathological states in various phases and stages. Disease interference changes the classical clinical picture, increases the number of complications and their severity, affects the quality of life and prognosis, as a result - complicated medical diagnostic process and reduced compliance. The presence in the elderly both mental and physical illness significantly affects the quality of life. Psychological interventions aimed at a patient's awareness of the disease and methods of its treatment, the creation of therapeutic alliance and the prevention of self-medication, according to our hypothesis, contributes to compliance and quality of life improvement in polymorbid elderly patients suffering from mental disorders. Methods. In the study took part 325 patients who underwent inpatient treatment at the gerontopsychiatric department and signed provided informed consent. The study had a design of a randomized controlled clinical trial. Patients were randomized to experimental and control groups in a ratio of 3 to 1 based on age and gender. The study group of 238 people received standard treatment and psychological interventions. A comparison group of 87 people had only standard treatment. Patients were evaluated for quality of life with SF-36 scale and compliance with Morisky Medication Adherence Scale. Results. We have seen significant intergroup differences on the Morisky Medication Adherence Scale in the baseline period. Consequently, its results were not be taken into account in the final analysis. Before treatment patients’ quality of life between the study groups did not differ statistically (p = 0.317). After the treatment, a statistically significant difference in life quality between experimental and control groups was found (p <0.001). A strong direct correlation was noted between changes in quality of life in SF-36 scale (rs = 0.5; p <0.001) and clinical treatment group, which included the patient. Patients with a younger age demonstrated a more significant improvement in their quality of life (r = -0.149; p = 0.007). A greater improvement in life quality was observed in patients with a lower cognitive function deficit in the MMSE score (r = 0.282; p <0.001). Among the self-treated patients, there were significant changes in SF-36 score after treatment (rs = 0.119; p = 0.033). The obtained data confirm that psychotherapeutic interventions (psychoeducation, compliance therapy, and pharmacomania prevention training) contribute to the life quality improvement of gerontopsychiatric patients. Conclusion. Usage of the psychotherapeutic program during standard treatment, aimed at the psychoeducation, creation of a therapeutic alliance and the reduction of pharmacomania (especially with regard to self-medication with barbiturates) promoted positive changes in the quality of life in the study sample. Our data confirm the need for interventions designed for improving the quality of life in the polymorbid elderly patients with mental disorders.